2021
DOI: 10.1177/1477370821997339
|View full text |Cite
|
Sign up to set email alerts
|

Explaining post-prison rehabilitation through music from the Good Lives Model perspective

Abstract: Whereas many research studies have discussed the impact of music programmes in a prison setting, few studies have investigated the impact of music programmes that take place outside the prison and are intended for formerly incarcerated individuals. The current study aims to fill this void by examining the experience of formerly incarcerated individuals who participated in a group music programme intended to assist them on their journey towards rehabilitation. Five formerly incarcerated individuals who particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Participants described the programme as an opportunity to express themselves and their emotions, feel positive about themselves and help them cope emotionally. It is interesting that improvements in well-being were not documented in previous research with former Sounding Out participants (five years after participation: Bensimon, 2021), suggesting this might be a short-term impact. Numerous studies suggest that participation in creative programmes can provide an effective way of dealing with challenging emotions (cf Nugent and Loucks, 2011; Blacker and Watson, 2008).…”
Section: Discussion Of Findingsmentioning
confidence: 85%
See 4 more Smart Citations
“…Participants described the programme as an opportunity to express themselves and their emotions, feel positive about themselves and help them cope emotionally. It is interesting that improvements in well-being were not documented in previous research with former Sounding Out participants (five years after participation: Bensimon, 2021), suggesting this might be a short-term impact. Numerous studies suggest that participation in creative programmes can provide an effective way of dealing with challenging emotions (cf Nugent and Loucks, 2011; Blacker and Watson, 2008).…”
Section: Discussion Of Findingsmentioning
confidence: 85%
“…The participant facilitator relationship is also particularly powerful and provides new role models (De Viggiani et al, 2013). The professional relationship and bonds between staff, musicians and participants builds on previous findings with Sounding Out (Bensimon, 2021) and other research in criminal justice settings. Cursley and Maruna (2015), for example, found that relationships between facilitators and participants increased social support, while De Viggiani et al (2013) have noted the new positive role models found in peers and facilitators.…”
Section: Interpersonal Relationshipsmentioning
confidence: 77%
See 3 more Smart Citations